Diamond is a scientist’s best friend : Counteracting systemic inequality in open access publishing - Mos, Maria; van Beuningen, Catherine; González, Paz; Hornikx, Jos; Steinkrauss, Rasmus (Dutch Journal of Applied Linguistics, 2024)
The field of applied linguistics is increasingly adopting open science practices. As open access publication gains traction, ethical issues emerge that need to be addressed by the field. This viewpoint paper addresses the concern that open science is not equally open for everyone. This paper describes how open access publication is increasingly being commercialized and explains how open access publication coincides with systemic inequality. We offer the following viewpoints for the field to consider:• We are morally obligated to make our research output accessible.• Hybrid, Gold, and Green open access publishing lead to systemic inequality in open access publishing, benefiting commercial publishers and those working in research-intensive universities and rich countries.• Diamond open access publication removes the systemic inequalities; hence, Diamond open access should be prioritized over Hybrid, Gold, and Green open access publication models.• We should move away from publish-and-read agreements and Green open access publishing, because they prevent system change.• Through our choices in our work as researchers, editors, reviewers, authors and teachers, we can contribute to the transition towards truly equitable open access publishing practices.• Senior researchers are in the position and have the moral obligation to be drivers of these changes.